Pemanfaatan Zat Warna Alam Kayu Jambal (Pelthophorumferugineum) sebagai Sensitizer pada Sel Surya Fotoelektrokimia - Khairi, Syahrul (ELKHA : Jurnal Teknik Elektro, 2016)
Abstract– The Natural dye of Jambal wood (Pelthophorumferugineum) was used as sensitizer in the fabrication of dye sensitizer solar cell (DSSC). The dye was extracted by using solid-liquid extraction method with ethanol as a solvent. UV-Vis spectrophotometer was used to measure the absorbance of dye solution. TiO2 thin-layer was prepared by slip coating method which the pH 5 suspension of TiO2 Degussa on HCl deposited on a glass substrate Fluorine-doped Tin Oxide (FTO).Dye adsorption was done by the immersion TiO2 thin layer in the dye solution in ethanol for 24 hours after calcination, then used as the working electrode. Counter electrode was prepared by the deposition of gold on the glass substrate.The performance of solar cells sensitized of natural Jambal wood dye was investigated through the measurements of Isc (short circuit currents) and Voc (open circuit voltage on) during irradiation with sun simulated Philips Powertone lamp. The measurement results showed that the solar cell has Isc and Voc by 56 ηA/cm2 and 394 mV respectively. Keywords– Fotoelektrokimia, Dye Sensitized Solar Cell, zatwarnaalam, Jambal.